The Evaluation of the Electronic Voting System: a Review - Hamisi Mtepa, Juma; Abiodun Akintola, Ismail; Salem Muftah, Ahmed; Hussain, Azham (International Journal of Engineering and Technology, 2026)
Electronic voting a ballot or e-casting a ballot alludes to the utilization of electronic methods in the decision procedure. It very well may be remotely done over the web or physically in surveying stations. Numerous nations have received this innovation for casting a ballot. The utilization of the e-casting a ballot framework is vital to improve the casting a ballot procedure. Specialists in e-casting a ballot ease of use assessment process have recommended three normal measurements for ease of use testing, which are viability, effectiveness and fulfillment.After the review of e-voting usability evaluation, it has been seen that researchers have concentrated on three main methodologies, which are review from experts, laboratory experiments and natural experiments. Among the 50 articles reviewed, about 50% of the e-voting system use touch screen interface; 17% use paper ballots and an optional scanner; another 17% use dial and buttons to pull the vote; while the rest, which is 16%, provide the whole ballot and request for the voter to press the button only once.
Keywords: Electronic Voting; Usability; Review.